A rare case of Takayasu’s arteritis in pregnancy - Singh, Sanjay; Kohli, Uttara Aiyer; Biswas, Manash; Singh, Moman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Takayasu’s arteritis (TA) is an uncommon, chronic inflammatory vascular disease of unknown etiology that primarily involves aorta and its branches and pulmonary arteries. Though it is present worldwide, it is more prevalent in Asian countries. It usually presents during reproductive age group with non-specific symptoms. The symptoms of the disease are varied and patients can present asymptomatically with impalpable pulses. There are no specific laboratory tests to diagnose TA. Angiographic imaging is considered to be the gold standard investigation in diagnosing TA. Steroids with subsequent tapering doses are the mainstay of medical treatment. Reconstructive vascular surgery is limited to the severe and irreversible stenotic lesions. Though the disease process theoretically is not aggravated by the pregnancy, development of preeclampsia and fetal growth restriction may occur during pregnancy. Preconception counseling and careful monitoring of pregnant mother by a multidisciplinary team, improves the pregnancy outcome. Here we present a bad obstetric case with TA who subsequently developed severe preeclampsia and fetal growth restriction. The pregnancy outcome could be made favourable by strict monitoring and multidisciplinary team approach.